Posttraumatic transdiaphragmatic intercostal hernia: report of a case and review of the literature. - Kalles, Vasileios; Dasiou, Maria; Doga, Georgia; Papapanagiotou, Ioannis; Konstantinou, Evangelos A; Mekras, Alexandros; Mariolis-Sapsakos, Theodoros; Anastasiou, Nikolaos (Int Surg, 2015)
Intercostal hernias are rare, and usually occur following injuries of the thoracic wall. The scope of this report is to present a case of a 53-year-old obese patient that developed a transdiaphragmatic intercostal hernia. The patient presented with a palpable, sizeable, reducible mass in the right lateral thoracic wall, with evident bowel sounds in the area, 6 months after a motor-vehicle accident. On computed tomography (CT), the hernia sac contained part of the liver and part of the ascending colon. A surgical repair of the defect was performed, using a prosthetic patch. The patient's postoperative course was uneventful and she remains recurrence free at 12 months after surgery. Intercostal hernias should be suspected following high-impact injuries of the thoracic wall, and CT scans will facilitate the diagnosis of intercostal hernia. We consider the surgical repair of the defect, with placement of a prosthetic mesh, as the treatment of choice to ensure a favorable outcome.
Keywords: Female; Hernia, Diaphragmatic, Traumatic; Herniorrhaphy; Humans; Middle Aged; Surgical Mesh; Thoracic Injuries; Thoracic Wall